(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the basic methods of determining the linguistic status of neologism and its relation to the concept of «occasionalism»; the author determines a criterium of novelty as an unadapted, unique and exceptional qualitative condition characterized by its position as a work without comparison.